Recent Progress and Advances in Stimuli-Responsive Polymers for Cancer Therapy - Rao, N. Vijayakameswara; Ko, Hyewon; Lee, Jeongjin; Park, Jae Hyung (Frontiers in Bioengineering and Biotechnology, 2018)
The conventional chemotherapeutic agents, used for cancer chemotherapy, have major limitations including non-specificity, ubiquitous biodistribution, low concentration in tumor tissue, and systemic toxicity. In recent years, owing to their unique features, polymeric nanoparticles have been widely used for the target-specific delivery of drugs in the body. Although polymeric nanoparticles have addressed a number of important issues, the bioavailability of drugs at the disease site, and especially upon cellular internalization, remains a challenge. A polymer nanocarrier system with a stimuli-responsive property (e.g., pH, temperature, or redox potential), for example, would be amenable to address the intracellular delivery barriers by taking advantage of pH, temperature, or redox potentials. With a greater understanding of the difference between normal and pathological tissues, there is a highly promising role of stimuli-responsive nanocarriers for drug delivery in the future. In this review, we highlighted the recent advances in different types of stimuli-responsive polymers for drug delivery.